MAIN WAYS OF EXPRESSING MODALITY IN THE MODERN ENGLISH LANGUAGE - Suyunova , Hayriniso (Educational Research in Universal Sciences, 2023)
The present article is devoted to investigation of ways of expressing modality in English. This or that meaning is to a great degree determined by communicative type of the sentence and the form of the infinitive. That is a huge problem for foreign learners of English, who make a great deal of mistakes in this field. So, the aim of the work is to show how modal verbs can be used and expressed in different situations and meanings.